Developments of the Estonian Competition Policy in the Framework of Accession to the European Union - Jüri Sepp; Diana Eerma (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2005)
In the article the abovementioned objectives are observed in four parts. The first part of the article gives a short overview about the competition creation through the market entry regulation in general. In the second part, the enterprise activity is treated proceeding from blocking the private restrictions in Estonia, showing the formation of the policy and problems. The following, third part, analyzes competition creation in exceptional spheres from viewpoints of regulation and deregulation. The fourth part of the article deals with publicly originated competition restrictions, especially connected with state aid, which influences the competition.
urn:nbn:de:gbv:705-opus-16953
Keywords: 330; Wettbewerbspolitik; EU-Erweiterung; Estland